Gene expression profile in chronic mouse liver injury caused by long‐term exposure to CeCl3. Issue 7 (9th November 2012) - Cheng, Jie; Fei, Min; Fei, Min; Sang, Xuezi; Sang, Xuezi; Cheng, Zhe; Gui, Suxin; Zhao, Xiaoyang; Sheng, Lei; Sun, Qingqing; Hu, Renping; Wang, Ling; et al.
<x xml:space="preserve">Abstract</x> Numerous studies have demonstrated lanthanide (Ln) accumulation in the liver, and the corresponding damage; however, very little work has been done to evaluate the relationship between Ln‐induced liver injury and its gene expression profile in mice. In this study, liver injury and gene‐expressed profiles in male mice induced by oral administration of CeCl3 (2 mg/kg) via gavage for 90 consecutive days were investigated. The results showed that cerium accumulation, liver inflammation, and hepatocyte necrosis were observed. CeCl3 exposure significantly decreased the counts of white blood cells, lymphocyte, and platelet, the reticulocyte count (Ret) and neutrophilic granulocyte percentages as well as A/G ratio, whereas markedly increased the activities of alkaline phosphatase, lactate dehydrogenase, and cholinesterase, and the concentrations of triglycerides and total cholesterol. Furthermore, microarray results of liver showed that the differential expression of 675 known function genes involved in immune/inflammation response, apoptosis, metabolic process, cell cycle, cell proliferation, cytoskeleton, oxidative stress, signal transduction, transcription, translation, and transportation in CeCl3 exposed livers, respectively. Specifically, the significant downregulation of Nt5e led to inflammation, overexpressed Cyp4a12a and great suppression of Cdkn1a resulted in hepatocyte apoptosis, marked elevation of Cel, and Cyp7b1 expression caused the metabolic disorders in mouse liver after long‐term CeCl3 exposure. Therefore, these genes may be in great relation to liver damages induced by exposure to CeCl3. © 2012 Wiley Periodicals, Inc. Environ Toxicol 29: 837–846, 2014.